Multimodality diagnosis of cardiac involvement in COVID-19 patients - Anca Balinisteanu; Hayat Memis; Gratiela Postulache-Cosmulescu; Diana Mihalcea; Sorina Mihaila; Dragos Vinereanu (Sciendo, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), exhibits a wide spectrum of manifestations, from asymptomatic presentations to acute respiratory failure, myocardial injury, arterial or venous thrombosis, multiorgan failure, and death. Although COVID-19 mainly disrupts the respiratory syndrome, it has been shown to have detrimental impact on cardiac morphology and function, resulting in a broad range of cardiovascular complications and poor outcome, increasing morbidity and mortality of these patients. This review will summarize the knowledge on characterization of myocardial injury in COVID 19, by using cardiac biomarkers, electrocardiographic, and cardiac multi-modality imaging findings for an early and accurate diagnosis, proper management, correct treatment, and follow-up of COVID-19 patients.